O tutorial do ciberespaço : engendramentos de uma técnica de ensino contemporânea - Reis, Luzo Vinicius Pedroso (2012)
This work analyzes how the tutorials in cyberspace engender new learning spaces and times and contribute to the production of the contemporary world, with their velocity and movement. In this sense, we understand a tutorial as a technique, as a human dimension. As traditional school produces a certain kind of society (The disciplinary society), the current techniques of distance education (e-learning) and on a radical way, tutorials participate in the production of the society of open and continuous control. Underneath these tuition procedures there are technical objects that operate, in relation to subjects either confinement and discipline (traditional school), or controlled movement (tutorials from cyberspace), specially now with semantic web. We start from the observation of the operation of the machines and subjects to understand the actual human-technique agency. An agency that highlights the characteristics of movement, the filtering procedures and the search for information.